ATF3 Prevents Stress-Induced Hematopoietic Stem Cell Exhaustion - Liu, Yufeng; Chen, Yingying; Deng, Xiaohui; Zhou, Jie (Frontiers in Cell and Developmental Biology, 2020)
Protection of hematopoietic stem cells (HSCs) from exhaustion and effective regeneration of the HSC pool after bone marrow transplantation or irradiation therapy is an urgent clinical need. Here, we investigated the role of activating transcription factor 3 (ATF3) in steady-state and stress hematopoiesis using conditional knockout mice (Atf3fl/flVav1Cre mice). Deficiency of ATF3 in the hematopoietic system displayed no noticeable effects on hematopoiesis under steady-state conditions. Expression of ATF3 was significantly down-regulated in long-term HSCs (LT-HSCs) after exposure to stresses such as 5-fluorouracil challenge or irradiation. Atf3fl/flVav1Cre mice displayed enhanced proliferation and expansion of LT-HSCs upon short-term chemotherapy or irradiation compared with those in Atf3fl/fl littermate controls; however, the long-term reconstitution capability of LT-HSCs from Atf3fl/flVav1Cre mice was dramatically impaired after a series of bone marrow transplantations. These observations suggest that ATF3 plays an important role in preventing stress-induced exhaustion of HSCs.